Exploring students perceptions of teaching, social, cognitive presences, effectiveness for teamwork and learning outcomes - Yussiff, A.-S. (Asian Research Publishing Network, 2015)
The three elements of the Community of Inquiry (CoI) Model which is known as teaching, social and cognitive presences can lead to successful educational experiences in a computer mediated online environment. However, current research has shown mixed-findings and little empirical evidences in supporting these elements leads to deep and meaningful learning outcomes. This study aims at investigating the relationships among students' perceptions of CoI elements, effectiveness for teamwork and students learning outcomes through pre-post-tests. Experimental research design consisting of experimental and control groups were conducted through the use of an e-collaboration environment and traditional-in-class-collaboration respectively by the two groups. Data was collected using CoI and effectiveness questionnaires, pre-test and post-test questions. The results from multiple regression and correlation analyses show that the values of the Pearson's correlation of five variables, R and R2 are positive and statistically significant. These results confirmed the statistical relationship among the five variables to be positive and significant. The results also demonstrated that the linear combination of the four predictors' variables strongly predicts the learning outcomes. These results have confirmed the relationship among the three elements of CoI, effectiveness for teamwork and student's learning outcomes.